Preparation and characterization of glass polyalkenoate cement with modified montmorillonite - Md Nasir, Nur'izzah (2014)
Glass polyalkenoate cement (GPC) is a water based cement which is formed by acid base reaction with poly(acid) and aluminosilicate glass. Glasses with vary amount of phosphate were prepared with compositions 4.5SiO2-3Al2O3-2CaF2-3CaO-xP2O5, where x=0, 0.75, 1.5, 3, and 4.5 using the hot melting technique. Sodium montmorillonite (Na-MMT) was modified into cationic (Mg, Al, Ca) and organo MMTs (12-aminoddodecanoic acid, ADA and octadeylamine, ODA). Selected MMTs were introduced to the GPC formulation and the setting reaction of the GPCs was studied using the FTIR spectroscopy. Cements were divided into GPC, GPC with addition of Na-MMT, and GPC with addition of modified Na-MMT (GPC+ODA-MMT/GPC+Al-MMT). The XRD patterns of all glasses showed amorphous phase except for IU45 glass (x=4.5 mole P2O5). XRD pattern for IU45 glass showed few sharp crystalline peaks, which is well-matched with AlPO4. 27Al MAS-NMR for all glasses except IU45 glass showed only the present of aluminium ions in 4- fold coordination with oxygen. While, for IU45 glass showed the aluminium ions present in 4- and 6- fold coordination with oxygen, which corresponded to the presence of AlPO4. FTIR spectrum for IU45 glass showed strong band at the 1080 - 1110 cm-1 region, which corresponded to the P–O stretch of the structural PO4 groups. Combination of XRD, MAS-NMR and FTIR results showed that the crystal in IU45 glass was AlPO4. For the cement part, FTIR spectrum showed the shoulder band at 950 cm-1 may be due to the formation of hydrated silica gel (Si-O(H) stretch) and the new band at 1560 cm-1 corresponded to the cross linking band (COO-M+). The shoulder band can only be observed in the earlier reaction of GPC and disappeared with time. Cross linking reaction caused the bending vibrations of C-H2 and CH-C=O at 1440 cm-1 and 1415 cm-1, respectively were slightly shifted to higher wave number. The carboxylic acid peak for GPC+Al-MMT disappeared slightly faster compared with GPC+ODA-MMT, GPC and GPC+Na-MMT. In compressive strength test, GPC+ODA-MMT and GPC+Al-MMT gave highest strength (75 – 85 MPa) at the beginning of setting reaction while GPC+Na-MMT gave the lowest strength (45.5 MPa). However, the strength of GPC+Na-MMT increased rapidly after 1 day aging time and kept increasing until 28 days. This study suggested that GPC+Al-MMT was slightly sped up the setting reaction while GPC+modified Na-MMT increased the compressive strength at early stage of the GPC setting reaction.